Evaluating the Evidence for Historical Interventions Having Reduced HIV Incidence : A Retrospective Programmatic Mapping Modelling Analysis - Synopsis Report 2016 - World Bank Group (World Bank, Washington, DC, 2016)
This multi-country study focuses on evaluating whether ART scale-up and changes in sexual risk behavior have contributed to the declining trends of HIV incidence and prevalence. The World Bank, UNAIDS, UNFPA, WHO, the Global Fund, and Imperial College London agreed upon specific criteria used to identify Botswana, Dominican Republic, Kenya, Malawi and Zambia as the five countries engaged in this study. Within Botswana, there was strong evidence that showed that ART and changes in sexual risk behavior had an impact of averting 210,000 infections in urban areas as 120,000 infections in rural areas (1975-2012). This discrepancy between urban and rural area results was thought to be due to geographical heterogeneity in HIV epidemiology or lack of power in available data. The changes in sexual risk behavior had a comparatively larger impact on the epidemic than ART, averting approximately 460,000 cumulative infections between 1982 and 2015. ART alone was found to be insufficient to explain the observed trend (approx. 44,000 FSW infections averted, 33,000 Bataeyes, and 28,000 amongst MSM). Results from Kenya showed that again that changes in sexual risk behavior, and to a much lesser extent ART, had averted approximately 4,107,000 infections between 1980-2015. An important takeaway from these results was that ART had marginal impact on prevalence trends but that it has yet to be fully optimized.